2018
DOI: 10.1096/fj.201800055r
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PFAL promotes lung fibrosis through CTGF by competitively binding miR‐18a

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, fibrotic parenchymal lung disease of unknown etiology and lacks an effective intervention. Long noncoding RNAs (lncRNAs) participate in organ fibrosis and various pulmonary diseases, but the role of lncRNAs in lung fibrosis is not fully understood. In the present study, we identified that lncRNA NONMMUT021928, designated as pulmonary fibrosis-associated lncRNA (PFAL), was up-regulated in the lungs of mice with experimental lung fibrosis, and in TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Jiang et al showed that inhibition of pulmonary fibrosis-regulatory lncRNA (PFRL) prevents pulmonary fibrosis by disrupting the miR-26a/smad2 loop [34]. In addition, another lncRNA, pulmonary fibrosis-associated lncRNA (PFAL) was found to be upregulated during lung fibrosis in vitro and in vivo fibrosis models [35]. Mechanistically, PFRL promoted lung fibroblast activation by acting as a competing endogenous RNA for miR-18a.…”
Section: The Role Of Mirna In Ipfmentioning
confidence: 99%
“…Jiang et al showed that inhibition of pulmonary fibrosis-regulatory lncRNA (PFRL) prevents pulmonary fibrosis by disrupting the miR-26a/smad2 loop [34]. In addition, another lncRNA, pulmonary fibrosis-associated lncRNA (PFAL) was found to be upregulated during lung fibrosis in vitro and in vivo fibrosis models [35]. Mechanistically, PFRL promoted lung fibroblast activation by acting as a competing endogenous RNA for miR-18a.…”
Section: The Role Of Mirna In Ipfmentioning
confidence: 99%
“…Previous studies revealed that lncRNAs participate in various cellular processes and that the dysregulation of lncRNAs usually leads to the o development of diseases, such as cancer [14] and cardiovascular diseases [15]. Moreover, several studies indicated that certain lncRNAs, such as PFAR [16], lncITPF [17], PFRL [18] and PFAL [19], act as important regulators in the progression of IPF. However, the exact functions of lncRNAs in IPF remain elusive.…”
mentioning
confidence: 99%
“…The lncRNA, DNM3OS (dynamin 3 opposite strand) and its relevant miRNA, display differential expression in experimental or clinical conditions [72]. lncRNA NONMMUT021928, designated as a pulmonary fibrosis-associated lncRNA (PFAL), promotes cell propagation, migration, motility and fibroblast-myofibroblast transition processes by competitively binding to miR-18a [73]. The lnc-PCF accelerates the propagation of epithelial cells through the complementary binding of miR-344a-5p, which has the target gene map3k11 [74].…”
Section: The Role Of Circrna In the Development Of Ipfmentioning
confidence: 99%
“…An exon circRNA with 1.2 kb, derived from the mammalian sex determination gene, may serve as a miR-138 sponge in the regulating process [57]. Furthermore, hsa_circRNA_100906 can bind to miR3245p/ miR3305p and hsa_circRNA_102348 can directly interact with miR630, both of which are downregulated in IPF [73]. Zhang et al [79] reported that miR3385p matches with hsa_circRNA_102101 and 102100 to regulate the coding gene CDC27, in IPF.…”
Section: The Role Of Circrna In the Development Of Ipfmentioning
confidence: 99%
See 1 more Smart Citation